Determination of Biosorption Behavior and Removal of Cationic Dyes by Phyllanthusemblica Fruit Stone - Sarita Kushwaha, Suhas, Shubham Chaudhary, Monika Chaudhary (International Journal of Advanced Science and Technology, 2020)
Biosorption of cationic dyes azure C, methylene blue and methylene green on to phyllanthusemblica fruit stone has been carried out as a function of contact time, initial dye concentration and temperature in order to find out the equilibrium, thermodynamic and kinetic parameters. The biosorption process in case of all the cationic dyes was initially fast and achieved the equilibrium within 120 min. The equilibrium data fitted well to both Langmuir as well as Freundlich isotherm model. The thermodynamic studies show that the biosorption was spontaneous and endothermic in nature. The kinetics studies for the biosorption was analyzed and showed that pseudo-second-order kinetic model fitted very well with the experimental data.